Gestational Medication Use, Birth Conditions, and Early Postnatal Exposures for Childhood Asthma - Yang-Ching Chen; Ching-Hui Tsai; Yungling Lee (Clinical and Developmental Immunology)
Our aim is to explore (1) whether gestational medication use, mode of delivery, and early postnatal exposure correlate with childhood asthma, (2) the dose responsiveness of such exposure, and (3) their links to early- and late-onset asthma. We conducted a matched case-control study based on the Taiwan Children Health Study, which was a nationwide survey that recruited 12-to-14-year-old school children in 14 communities. 579 mothers of the participants were interviewed by telephone. Exclusive breastfeeding protected children from asthma. Notably, childhood asthma was significantly associated with maternal medication use during pregnancy, vacuum use during vaginal delivery, recurrent respiratory tract infections, hospitalization, main caregiver cared for other children, and early daycare attendance. Exposure to these factors led to dose responsiveness in relationships to asthma. Most of the exposures revealed a greater impact on early-onset asthma, except for vacuum use and daycare attendance.